Disclosure of Provisions as Prior Period Errors: A Case Study from Poland - Jaroslaw SZYSZKA (Communications of International Proceedings, 2025)
In his practical experience, the Author has often encountered the issue of provisions. During business consultations, the Author often encountered cases in which provisions are not created. There are many reasons for this situation – from lack of knowledge about the need to estimate them, through the lack of ability to reliably estimate the date or value of provisions, to, unfortunately, cases of deliberate failure to report them. Therefore, the subject of the research are provisions and the moment of their disclosure. In one of the cases that the Author has encountered the entity didn’t recognize the obligation to create provisions that happened in previous financial years. The discussion with the capital group CFO and with the auditor provided to ask the question: should the current estimation of provision be treated as a new disclosure or can it be assumed that the fact of not creating a provision is the result of a prior period error? That is also the main research problem of the paper. For practical purposes analyzed Standards did not provide a clear answer to the following question. Therefore, the Author did an analysis of the literature on the subject, also not finding a clear answer. In the Author's opinion, such a situation is a void that should be filled and should result in further scientific discussion. After using the literature analysis method, combined with the dogmatic-legal analysis method, the Author carried the works using analysis and synthesis to try to formulate a scientific solution. Finally, based on a case study, The Author presented a practical solution to this problem, which can be helpful for business. In the Author's opinion, neither accounting theory nor current accounting standards prevent, in the case when the provision should have been disclosed in prior periods, its disclosure as a prior periods error.
Keywords: Provisions; financial reporting; errors